Early Squamous Cell Carcinoma of the Anal Canal Resected by Endoscopic Submucosal Dissection - Tamaru, Yuzuru (Case Rep Gastroenterol, 2015)
The standard treatment approach for squamous cell carcinoma (SCC) of the anal canal includes abdominoperineal resection and chemoradiotherapy. However, there are currently very few reports of early SCC of the anal canal resected by endoscopic submucosal dissection (ESD). We report 2 rare cases of SCC of the anal canal resected by ESD. In case 1, a 66-year-old woman underwent a colonoscopy due to blood in her stool, and an elevated lesion, 15 mm in size, was identified from the rectum to the dentate line of the anal canal on internal hemorrhoids. The lesion was diagnosed as an early SCC of the anal canal, and ESD was successfully performed. The histopathological diagnosis was SCC in situ. In case 2, a 71-year-old woman underwent a colonoscopy due to constipation, and an elevated lesion, 25 mm in size, was identified from the dentate line to the anal canal. The lesion was diagnosed as early-stage SCC of the anal canal, and ESD was successfully performed. The histopathological diagnosis was SCC in situ. No complications or recurrence after ESD occurred in either case.